Synthesis of Carlina Oxide Analogues and Evaluation of Their Insecticidal Efficacy and Cytotoxicity - Spinozzi, Eleonora; Ferrati, Marta; Baldassarri, Cecilia; Maggi, Filippo; Pavela, Roman; Benelli, Giovanni; Aguzzi, Cristina; Zeppa, Laura; Cappellacci, Loredana; Palmieri, Alessandro; Petrelli, Riccardo (Journal of natural products, 2023)
Compounds isolated from botanical sources represent innovative and promising alternatives to conventional insecticides. Carlina oxide is a compound isolated from Carlina acaulis L. (Asteraceae) essential oil (EO) with great potential as bioinsecticide, being effective on various arthropod vectors and agricultural pests, with moderate toxicity on non-target species. Since the production from the wild source is limited, there is the need of exploring new synthetic routes for obtaining this compound and analogues with improved bioactivity and lower toxicity. Herein, the chemical synthesis of carlina oxide analogues was developed. Their insecticidal activity was assessed on the vectors Musca domestica L. and Culex quinquefasciatus Say, and their cytotoxicity was evaluated on a human keratinocyte cell line (HaCaT). The compounds' activity was compared with that of the natural counterparts EO and carlina oxide. In housefly tests, the analogues were comparably effective to purified carlina oxide. In Cx. quinquefasciatus assays, the meta-chloro analogue provided a significantly higher efficacy (LC50 of 0.71 μg mL-1) than the EO and carlina oxide (LC50 1.21 and 1.31 μg mL-1, respectively) and a better safety profile than carlina oxide on keratinocytes. Overall, this study can open the way to an agrochemical production of carlina oxide analogues employable as nature-inspired insecticides.
Keywords: Asteraceae; Oils, Volatile; insekticidy; Larva; komáří přenašeči; Animals; Humans; lidé; oleje prchavé; Mosquito Vectors; zvířata; Culex; Insecticides; larva